Mechanistic aspects of methanol electro-oxidation reaction through cyclic voltammetry: is it correct to blame carbon monoxide for catalyst poisoning? - Deshpande, Pooja S.; Chaudhari, Vijay R.; Prasad, Bhagavatula L. V. (Energy Technology, 2020)
The mechanism of the methanol oxidation reaction is revisited using systematic cyclic voltammetric studies. These studies clearly indicate that the peak during the cathodic scan belongs mainly to electro-oxidation of the carbon monoxide, and that only a fraction of this carbon monoxide remains adsorbed on the electrode, contrary to what previous reports suggested. More details can be found in article number by Bhagavatula L. V. Prasad and co-workers.
Keywords: carbon monoxide; cyclic voltammetry; electrocatalysts; electrode poisoning; Methanol oxidation